A value of information framework for climate adaptation and risk-management - Frances C Moore; Adam Sobel (Environmental Research: Climate)
The demand for information required to manage weather-related risks under changing climate conditions is growing. In response there have been efforts within both the public and private sectors to provide information from climate science to support adaptation decisions. Such information provision is complicated by the wide range of potential adaptation use-cases, the variable spatial and temporal scales of information required, and the lack of a systematic understanding of how scientific uncertainties propagate through adaptation decisions to affect the value to users. Here we propose value of information (VOI) as a useful conceptual framework for analyzing information designed to support adaptive decision-making. We describe the VOI framework and its usefulness for the adaptation context. We illustrate using a stylized set of decisions and a set of climate information states based on a modified Lorenz model.